Implementation of Top Up & Refund Balance Application at FoodCourt - Agus Kusnawan; Irma Permatasari; Riki Riki (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2018)
effectiveness and efficiency in management of information systems are very important to determine the success and smoothness of the company. With the demands of transaction speed and ease of getting information. Waterfall is a method used in building this system, where the ease of use. With the application of a computerized system it is concluded that it can correct weaknesses and reduce the level of errors in making reports and To produce good reports, the transfer of data must be done carefully, because accuracy is expected to be required by the administration in data processing and also cooperation and a sense of responsibility. each personnel is expected to achieve maximum results.